Characterization of the complete mitochondrial genome of the Meiren yak (Bos grunniens) - Guo, Xian (Mitochondrial DNA B Resour, 2020)
In this study, high-throughput Illumina sequencing was employed to assemble the complete mitochondrial genome of the Meiren yak (Bos grunniens), a local yak breed from Gansu Province, China. The mitochondrial genome is 16,321 bp long with an A + T-biased nucleotide composition and harbors 13 protein-coding, 22 Trna, and 2 rRNA genes, and a noncoding control region. The mitogenomic organization and codon usage are highly similar to those of previously published congeneric mitochondrial genomes. Bayesian phylogenetic analysis indicates that Meiren yak is most closely related to nine other yak breeds (incl. Datong, Huanhu, Pali, Pamir, Polled, Qilian, Seron, Sunan, and Tianjun yaks).